2015
DOI: 10.1186/s40795-015-0011-0
|View full text |Cite
|
Sign up to set email alerts
|

Feeding of preschool children in Vietnam: a study of parents’ practices and associated factors

Abstract: Background: Understanding parents' feeding control practices and their associations with various factors is useful for prevention of childhood obesity, an emerging problem in low-and middle-income countries. The aim of this paper is to describe the control practices used by parents of preschool children in Vietnam and factors associated with these. Methods: Two cross-sectional studies were conducted in urban DodaLab (n = 1364) and rural FilaBavi (n = 1313), Health and Demographic Surveillance Sites (HDSS), Han… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
18
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 31 publications
3
18
0
1
Order By: Relevance
“…The moderate association between maternal education and child overweight or obesity, which is consistent with other studies in Vietnam [29], reveals a possible intervention point in the Vietnam education system [30], to raise awareness of the consequences of overweight and obesity and how to prevent them. This is particularly promising, given the recent rapid increase in education in Vietnam (the proportion of mothers with at least a high school education increased from 39.3% in 2012 to 49.1% in 2015).…”
Section: Discussionsupporting
confidence: 88%
“…The moderate association between maternal education and child overweight or obesity, which is consistent with other studies in Vietnam [29], reveals a possible intervention point in the Vietnam education system [30], to raise awareness of the consequences of overweight and obesity and how to prevent them. This is particularly promising, given the recent rapid increase in education in Vietnam (the proportion of mothers with at least a high school education increased from 39.3% in 2012 to 49.1% in 2015).…”
Section: Discussionsupporting
confidence: 88%
“…A cross-sectional study conducted with three- to six-year old children in Vietnam [28] examined the association of non-responsive parental feeding practices (i.e., restriction, pressure to eat, and monitoring of child food intake) and child weight status (BMI) and found that the mother’s perception of the child’s weight was negatively associated with pressure to eat and positively associated with monitoring. Furthermore, a positive association was found between the mother’s perception of the child’s weight and restriction.…”
Section: Resultsmentioning
confidence: 99%
“…Maternal education is linear to the ability of the mothers of health promotion behavior. The mother's education is one of the factors that determine the success of the parenting patterns present when feeding their children (Do et al, 2015;Goulding et al, 2014). In contrast, low maternal education results in poor health promotion behavior (Mulyani, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The education level of the mother determines the nutritional status of the child (Habibi, Zahra, Aguenaou, & Doukkali, 2018). The good education of the mother will have an impact on the pattern of giving good food to the child (Do, Eriksson, Tran, Petzold, & Ascher, 2015). Paying attention to social and demographic characteristics is an important factor for improving the child's nutritional status (Holbrook, White, Heyman, & Wojcicki, 2013).…”
Section: Introductionmentioning
confidence: 99%